Recent Advances on the Synthesis of C-Glycosides from 1,2-Glycals - Das, Ramanand; Das, Malati; Mukherjee, Debaraj; Kundu, Taraknath (Synthesis, 2024)
The development of stereoselective synthetic routes for C-glycosides has attracted immense attention from carbohydrate chemists over the last two decades. In this short review, progress made over the last decade towards the synthesis of C-glycosides using glycals as precursors is discussed. Glycals have been extensively manipulated to generate oxocarbenium cations or glycosyl anions for the formation of C–C bonds at the anomeric position through attack of C-nucleophiles or via transition-metal-catalyzed coupling reactions. Recent reports on carbon-Ferrier, intramolecular Cope, and Claisen rearrangements, along with various coupling reactions in the presence or absence of directing groups are evaluated herein. Contemporary applications of these reactions in the syntheses of natural products, drugs and scaffolds with bioactive potential are briefly discussed.1 Introduction2 Rearrangement Reactions2.1 Carbon-Ferrier Rearrangement2.2 Other Rearrangement Reactions3 C1 Coupling4 Annulations5 Addition Reactions6 Natural Product Synthesis7 Conclusion
Keywords: C-glycosides; 1,2-glycals; carbon-Ferrier rearrangement; coupling reactions; natural products; annulation